Law in the New Testament The @Parable of the Prodigal Son - Derrett, J. Duncan M. 1922-2012 (1967)
Luke xv. 11-32, an elaborate, circumstantial, in fact the longest, parable, calls now for the endeavours of a symposium. This paper cannot do more than open the legal aspects, which have already been handled by Professor David Daube and Professor Jean Dauvillier, and the symbolic aspects, which have been ignored. A complete investigation of the symbolism is not to be looked for until the midrashic links between the parable and its associated passages in Deuteronomy have been expounded by an expert in the technique of delivery of sermons amongst the Jews. Our parable's place in a lectionary cycle has been identified, and the implications of this also must be brought out: in part these will overlap with the work just alluded to, and in part they will reveal the early church's view of the parable's implicit significance. This work, however, will relate to the stage at which the parable became a written document, and to its worth for those who first used it in liturgy. This paper is concerned with Jesus’ own meaning, so far as we can rediscover it from the shape and content of the parable in the light of contemporary attitudes. Though this means covering ground already covered often, and much current exegesis will be confirmed, there is more by way of subtle statement and even more subtle contention in the parable than could have been realized before. Close studies of the vocabulary from Wetstein to J. Jeremias do not help us much at this stage of refinement; but it is interesting to note that in Jeremias's view, well substantiated as to the greater part of the parable, traces of the semitic origin of the document before us are visible throughout.